Unveiling the Nexus of Consumer Price Index, Economic Policy Uncertainty, Geopolitical Risks, and Gold Prices on Indonesian Sustainable Stock Market Performance - Darsono, Susilo Nur Aji Cokro; Muttaqin, Ecky Imamul; Rahmadani, Revy Andika; Nguyen, Tran Thai Ha (International Journal of Economics and Financial Issues, 2024)
This study contributes to evaluate capital market performances categorized as sustainable stocks in Indonesia. The aim of the proposed model is to examine the impact of the Consumer Price Index, Economic Policy Uncertainty, Geopolitical Risk, and Global Gold Prices on the SRI-KEHATI Index. The study will cover the study period from January 2017 to December 2022. The ARDL approach is employed to see impacts in both long-term and short-term. The findings indicate that in the short run, the variables Consumer Price Index and Geopolitical Risk have a notable positive impact on the SRI-KEHATI Index, while World Gold Prices have a substantial negative impact. However, the variable Economic Policy Uncertainty does not have a significant effect on the SRI-KEHATI Index. In addition, over an extended period of time, the variables of Economic Policy Uncertainty and Geopolitical Risk exhibit a notable and constructive impact on the SRI-KEHATI Index. Compared to the long-term impact of the Consumer Price Index on Gold Prices is negligible.